Clinical observation of low‐dose combination chemotherapy in refractory/recurrent paroxysmal nocturnal hemoglobinuria patients: A single‐center retrospective analysis. Issue 2 (14th January 2022) - Li, Liyan; Liu, Hui; Wang, Honglei; Liu, Zhaoyun; Chen, Yingying; Liu, Chunyan; Zhao, Xiaoyu; Li, Lijuan; Wang, Huaquan; Shao, Zonghong; Fu, Rong
Abstract: Background: We performed a retrospective analysis to investigate the clinical characteristics and therapeutic strategies of 20 refractory/recurrent PNH patients, including the clinical efficacy of chemotherapy treatment, safety, and survival. Methods: The clinical data of 20 classic PNH patients who were refractory/recurrent or had glucocorticoid dependence in our hospital were analyzed, including clinical manifestations, laboratory examinations, treatment efficacy, and survival. Results: Seventeen patients had a marked improvement in anemia after chemotherapy, 14 patients acquired blood transfusion independence, and the Hb of 3 patients increased to normal levels. Although 6 patients still needed blood transfusion, the transfusion interval was significantly prolonged. The percentages of LDH, TBIL, and RET, which are indicators of hemolysis, were significantly lower than those before chemotherapy. The dosage of adrenal glucocorticoids was reduced by more than half compared with that before chemotherapy. Conclusions: Chemotherapy can reduce PNH clones, promote normal hematopoiesis, and control hemolytic attack. It is a promising and widely used therapeutic method. Abstract : We performed a retrospective analysis to investigate the clinical characteristics and therapeutic strategies of 20 refractory/recurrent PNH patients, including the clinical efficacy of chemotherapy treatment, safety, and survival. The clinical data of 20 classic PNH patients that were refractory/recurrent or had glucocorticoid dependence in our hospital were analyzed, including clinical manifestations, laboratory examinations, treatment efficacy, and survival. Seventeen patients had a marked improvement in anemia after chemotherapy, 14 patients acquired blood transfusion independence, and the Hb of 3 patients increased to normal levels. Although 6 patients still needed blood transfusion, the transfusion interval was significantly prolonged. The percentages of LDH, TBIL, and RET, which are indicators of hemolysis, were significantly lower than those before chemotherapy. The dosage of adrenal glucocorticoids was reduced by more than half compared with that before chemotherapy. Chemotherapy can reduce PNH clones, promote normal hematopoiesis, and control hemolytic attack. It is a promising and widely used therapeutic method.